Pengaruh Konseling saat Persalinan terhadap Kepesertaan Keluarga Berencana Pasca Salin di Kabupaten Kolaka - Abbas, Marwan; Hadijono, Soerjo; Emilia, Ova; Hartono, Eddy (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: Death among repro ductive age women about 25-50% is caused by pregnancy related condition. Family Planning program is known as one pillar to control pregnancy. Counseling plays important roles to increase contraceptive prevalent rate.Objective: To assess the effectiveness of family planning counseling during latent phase of labor in increasing postpartum contraception.Method: The study was an experimental design which involved all primary health centre, Maternity Hospital and General hospital in Kolaka district in the period of 1 January 2016 to March 2016. Sampling included 108 subjects divided into intervention and control group. Selection of health facility into two groups was done through simple coin toss. Intervention was family planning counseling conducted during latent phase of labor using flipchart standardised by BKKBN in 2014.Result and Discussion: From all subjects, 70 (64.8%) decided to participate in post partum contraception. Participation for contraception was significantly higher in counseling group (92%) compare to control (37%) (p<0.001, RR 2.5; CI 1.75 – 3.57). Age and companion during labor did not influence contraception participation (p>0,05). There was a trend that contraception participation higher in older age. Other factors such as education, income, parity and previous conseling significantly influence contraception participation (p<0,05).Conclusion: Family planning counseling during latent phase increase the participation in postpartum contraception. Education, income, parity and previous counseling influence the participation in postpartum contraception.Keyword: Family Planning, Post partum contraception, Factors on contraception participation